(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Technology science plays a crucial role in shaping the future of our society. To fuel its growth and development, it is imperative to employ modern educational technologies that facilitate effective learning and knowledge acquisition. This article explores the potential of integrating modern educational technologies into the field of technology science, highlighting their benefits and discussing various approaches to their implementation. It also emphasizes the importance of fostering a collaborative environment that encourages innovation and multidisciplinary learning. By embracing these advancements, we can enhance the development of technology science and empower the next generation of technologists and scientists.